2015
DOI: 10.1586/17512433.2015.1011125
|View full text |Cite|
|
Sign up to set email alerts
|

Statins stimulate atherosclerosis and heart failure: pharmacological mechanisms

Abstract: In contrast to the current belief that cholesterol reduction with statins decreases atherosclerosis, we present a perspective that statins may be causative in coronary artery calcification and can function as mitochondrial toxins that impair muscle function in the heart and blood vessels through the depletion of coenzyme Q10 and 'heme A', and thereby ATP generation. Statins inhibit the synthesis of vitamin K2, the cofactor for matrix Gla-protein activation, which in turn protects arteries from calcification. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 49 publications
(22 reference statements)
2
80
1
5
Order By: Relevance
“…10,11,70,186,241,287,290,291 Following publication of reports of exaggerated side-effect rates, [10][11][12]70 and related media coverage, the Picker Institute conducted in-depth interviews and focus groups with patients, general practitioners, and cardiologists, along with online surveys, in 2015. 292 They found that the adverse media coverage was linked to increased reticence among the doctors to discuss and prescribe statins, and reduced compliance by the patients (including those with preexisting cardiovascular disease) due to raised awareness of perceived side-effects.…”
Section: Public Health Consequences Of Misleading Claims About the Samentioning
confidence: 99%
“…10,11,70,186,241,287,290,291 Following publication of reports of exaggerated side-effect rates, [10][11][12]70 and related media coverage, the Picker Institute conducted in-depth interviews and focus groups with patients, general practitioners, and cardiologists, along with online surveys, in 2015. 292 They found that the adverse media coverage was linked to increased reticence among the doctors to discuss and prescribe statins, and reduced compliance by the patients (including those with preexisting cardiovascular disease) due to raised awareness of perceived side-effects.…”
Section: Public Health Consequences Of Misleading Claims About the Samentioning
confidence: 99%
“…End points such as re-hospitalization, cardiac events, and non-fatal stroke would then be less objective than mortality rates for CVD or all causes. As pointed out previously [11, 81], the apparent effectiveness of statins for the prevention of ASCVD as reported in the literature changed drastically after new clinical trial regulations came into effect in 2004/2005 in the EU and US. After this point, no significant beneficial effects of statins for lowering objective end points have been reported [11, 81].…”
Section: Critical Review Of the Consensus Statement 2017 Based On Stamentioning
confidence: 90%
“…As pointed out previously [11, 81], the apparent effectiveness of statins for the prevention of ASCVD as reported in the literature changed drastically after new clinical trial regulations came into effect in 2004/2005 in the EU and US. After this point, no significant beneficial effects of statins for lowering objective end points have been reported [11, 81]. There are groups of scientists who claim that statins are effective for the prevention of ­ASCVD, which is based on meta-analyses including RCT reports published before 2004 – mainly in the 1990s.…”
Section: Critical Review Of the Consensus Statement 2017 Based On Stamentioning
confidence: 90%
“…Okuyama et al represented a perspective that statins stimulate atherosclerosis and heart failure [17]. The researchers said that statins stop the biosynthesis of vitamin K2 that serves as a cofactor for the activation of matrix Gla-protein.…”
Section: Editorialmentioning
confidence: 99%